Prospective Evaluation of Aspergillus fumigatus-Specific IgG in Patients With Cystic Fibrosis - Eschenhagen, Patience; Grehn, Claudia; Schwarz, Carsten (Frontiers in Cellular and Infection Microbiology, 2021)
Background In Cystic Fibrosis (CF), the airways are often colonized by opportunistic fungi. The most frequently detected mold is Aspergillus fumigatus (Af). Af diseases are associated with significant morbidity and mortality. The most common clinical picture caused by Af is allergic bronchopulmonary aspergillosis (ABPA), triggered by an immunological reaction against Af. Af bronchitis and invasive aspergillosis rarely occur in CF as a result of spore colonization and germination. Since pulmonary mycoses and exacerbations by other pathogens overlap in clinical, radiological, and immunological characteristics, diagnosis still remains a challenge. The search for reliable, widely available biomarkers for Af diseases is therefore still an important task today. Objectives Af-specific IgG m3 is broadly available. Sensitivity and specificity data are contradictory and differ depending on the study population. In our prospective study on pulmonary Af diseases in CF, we determined specific IgG m3 in order to test its suitability as a biomarker for acute Af diseases and as a follow-up parameter. Methods In this prospective single center study, 109 patients with CF were screened from 2016 to 2019 for Af-associated diseases. According to diagnostic criteria, they were divided into four groups (control, bronchitis, ABPA, pneumonia). The groups were compared with respect to the level of Af-specific IgG (ImmunoCAP Gm3). We performed a receiver operating characteristic (ROC) curve analysis to determine cut-off, sensitivity and specificity. Twenty-one patients could be enrolled for a follow-up examination. Results Of the 109 patients, 36 were classified as acute Af-disease (Af bronchitis, ABPA, Af pneumonia). Of these, 21 patients completed follow up-screening. The median Af-specific Gm3 was higher in the acute Af-disease groups. There was a significant difference in Af-specific IgG m3 compared to the control group without acute Af-disease. Overall, there was a large interindividual distribution of Gm3. A cut-off value of 78.05 mg/L for Gm3 was calculated to discriminate controls and patients with ABPA/pneumonia with a specificity of 75% and a sensitivity of 74.6%. The follow up examination of 21 patients showed a decrease of Gm3 in most patients without statistical significance due to the small number of follow up patients. Conclusion Af specific IgG may be a useful biomarker for acute ABPA and Af pneumonia, but not for Af bronchitis in CF. However, due to the large interindividual variability of Gm3, it should only be interpreted alongside other biomarkers. Therefore, due to its broad availability, it could be suitable as a biomarker for ABPA and Af pneumonia in CF, if the results can be supported by a larger multicenter cohort.